A Content Analysis of the Concepts and Images of the Physical Aging Primary School Textbooks in Iran - Zahra Eftekhari; Farhad Nosrati Nejad; Robabeh Sahhaf; Nosaybeh Zanjari (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives This study has two purposes. The first purpose is to analyze the concept of old age in the textbooks of the primary schools after the Islamic Revolution (1979). The second purpose is to study the type of images used in these textbooks to depict the elderly people in physical terms.  Methods & Materials This research is a descriptive Research to analyze the content of the books. The data is collected from a statistical population of all the primary schools’ textbooks used after the Islamic Revolution. Of them, the ones which were taught in 1979, 1996, 2006, and 2015 were selected as the samples because these books were subject to change in those years. The context units were Lessens and of analysis was the contents and pictures in which the concept of old age is presented.  Results The findings of this research show that the textbooks depict aged people as those with wrinkles (52.1%), grey or white hair (44.4%), upright stature (57%), and maintain good physical health (43%). These older adults are healthy (73.2%) and independents (72.5%). Most of them (64.1) never used any healthcare aids, and in case of health care tools, only spectacles are depicted.  Conclusion The results showed that the textbooks depict a positive image of the physical health of the older people. The picture in the textbooks shows elders’ natural status and their physical conditions in the old age. It is interesting to mention that during the first year post the Islamic Revolution, the illustrations showed the older adults as young. It’s natural considering the rise of maximum life expectancy in the recent decades, and it also reflects the realities of old age.